Is basic science disappearing from medicine? The decline of biomedical research in the medical literature. Issue 2 (14th October 2015) - Steinberg, Benjamin E.; Goldenberg, Neil M.; Fairn, Gregory D.; Kuebler, Wolfgang M.; Slutsky, Arthur S.; Lee, Warren L.
Abstract : Explosive growth in our understanding of genomics and molecular biology have fueled calls for the pursuit of personalized medicine, the notion of harnessing biologic variability to provide patient‐specific care. This vision will necessitate a deep understanding of the underlying pathophysiology in each patient. Medical journals play a pivotal role in the education of trainees and clinicians, yet we suspected that the amount of basic science in the top medical journals has been in decline. We conducted an automated search strategy in PubMed to identify basic science articles and calculated the proportion of articles dealing with basic science in the highest impact journals for 8 different medical specialties from 1994 to 2013. We observed a steep decline (40‐60%) in such articles over time in almost all of the journals examined. This rapid decline in basic science from medical journals is likely to affect practitioners' understanding of and interest in the basic mechanisms of disease and therapy. In this Life Sciences Forum, we discuss why this decline may be occurring and what it means for the future of science and medicine.—Steinberg, B. E., Goldenberg, N. M., Fairn, G. D., Kuebler, W. M., Slutsky, A. S., Lee, W. L. Is basic science disappearing from medicine? The decline of biomedical research in the medical literature. FASEB J. 30, 515‐518 (2016). www.fasebj.org